Dynamic correlations and volatility spillovers between Financial Stress, exchange rates and gold prices in BRICS - Yan,Liwen (2024)
The objective of this study is to investigate the dynamic correlations and volatility spillover effect between the financial stress index (FSI), exchange rates, and gold prices among Brazil, Russia, India, China and South Africa (BRICS countries) over the period between February 2014 and February 2024. The FSI is established using the principal component analysis approach for each country to evaluate the stress level of the financial market in BRICS countries. Two methods are employed to analyse time-varying correlation across markets: the vector autoregressive (VAR) model and the Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) model. Furthermore, we utilise an asymmetric Baba, Engle, Kraft and Kroner Generalized Autoregressive Conditional Heteroskedasticity (BEKK-GARCH) model to explore volatility spillovers and leverage effects among three markets. The results show that the FSI is remarkably autocorrelated, and the effects of exchange rates and gold on its volatility show heterogeneity across countries. In addition, using an asymmetric BEKK-GARCH model, we found that all three markets have significant leverage effects of their own, and exchange rates and gold prices have asymmetric volatility spillovers to the FSI for most countries.
Keywords: Dynamic conditional correlation; Volatility spillovers; Asymmetric effect; VAR; DCC-GARCH; BEKK-GARCH